2013
DOI: 10.1248/cpb.c12-00826
|View full text |Cite
|
Sign up to set email alerts
|

Niobium(V) Chloride Catalyzed Oxidation of Dithioacetals with 30% Hydrogen Peroxide: A Concise Preparation of Bissulfonylmethylene Compounds

Abstract: The oxidation of dithioacetals with 16 eq of 30% hydrogen peroxide in the presence of 10 mol% niobium(V) chloride at room temperature provides bissulfonylmethylenes in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There is precedence for the application of niobium catalysts in oxidative processes that employ hydrogen peroxide as oxidant. Most examples involve the epoxidation of alkenes [17], but oxidation of dithioacetals, benzylalcohols, naphthols and sulfides [17][18][19][20][21] have also been reported. Reddy and Sayari demonstrated that vanadium was capable of catalyzing the oxidation of amines in the presence of hydrogen peroxide to afford the corresponding imines and oximes under mild conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…There is precedence for the application of niobium catalysts in oxidative processes that employ hydrogen peroxide as oxidant. Most examples involve the epoxidation of alkenes [17], but oxidation of dithioacetals, benzylalcohols, naphthols and sulfides [17][18][19][20][21] have also been reported. Reddy and Sayari demonstrated that vanadium was capable of catalyzing the oxidation of amines in the presence of hydrogen peroxide to afford the corresponding imines and oximes under mild conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…The previous treatment with hydrogen peroxide should generate peroxo groups on the catalyst surface, which makes the catalyst more active. [18][19][20][21] It is interesting to observe that the catalyst without previous treatment with hydrogen peroxide (Nb-MCM) showed an increase in the removal of rhodamine B after 30 min, indicating that after that time the H 2 O 2 added to the reaction system reacted with the surface Nb forming the peroxo group in situ. This result shows clearly that the previous treatment of the catalyst with H 2 O 2 increases the catalytic activity of the silica modified with niobium for oxidation of the organic compound.…”
Section: Catalytic Testsmentioning
confidence: 99%